Melatonin enhances arsenic trioxide-induced cell death via sustained upregulation of Redd1 expression in breast cancer cells. (15th February 2016) - Yun, Sun-Mi; Woo, Sang Hyeok; Oh, Sang Taek; Hong, Sung-Eun; Choe, Tae-Boo; Ye, Sang-Kyu; Kim, Eun-Kyu; Seong, Min Ki; Kim, Hyun-A; Noh, Woo Chul; Lee, Jin Kyung; Jin, Hyeon-Ok; et al.
Abstract: Melatonin is implicated in various physiological functions, including anticancer activity. However, the mechanism(s) of its anticancer activity is not well understood. In the present study, we investigated the combined effects of melatonin and arsenic trioxide (ATO) on cell death in human breast cancer cells. Melatonin enhanced the ATO-induced apoptotic cell death via changes in the protein levels of Survivin, Bcl-2, and Bax, thus affecting cytochrome c release from the mitochondria to the cytosol. Interestingly, we found that the cell death induced by co-treatment with melatonin and ATO was mediated by sustained upregulation of Redd1, which was associated with increased production of reactive oxygen species (ROS). Combined treatment with melatonin and ATO induced the phosphorylation of JNK and p38 MAP kinase downstream from Redd1 expression. Rapamycin and S6K1 siRNA enhanced, while activation of mTORC1 by transfection with TSC2 siRNA suppressed the cell death induced by melatonin and ATO treatment. Taken together, our findings suggest that melatonin enhances ATO-induced apoptotic cell death via sustained upregulation of Redd1 expression and inhibition of mTORC1 upstream of the activation of the p38/JNK pathways in human breast cancer cells. Highlights: Melatonin enhanced the ATO-induced apoptotic cell death in breast cancer cells. Combined treatment with melatonin and ATO synergistically induced ROS generation in breast cancer cells. Melatonin enhances ATO-induced cell death via sustained upregulation of Redd1 in breast cancer cells. Combined treatment with melatonin and ATO caused a activation of p38 and JNK via expression of Redd1 in breast cancer cells.